Data Collection in Multiple Sclerosis: The MSDS Approach - Ziemssen, Tjalf; Kern, Raimar; Voigt, Isabel; Haase, Rocco (Frontiers in Neurology, 2020)
Multiple sclerosis (MS) is a frequent chronic inflammatory disease of the central nervous system which affects patients for decades. As monitoring and treatment of multiple sclerosis get more and more personalized and complex, the individual assessment and collection of different parameters ranging from clinical assessments via laboratory and imaging data to patient-reported data are necessary in an innovative patient management in MS. These points predestine electronic data processing for use in MS documentation. Such technologies enable the rapid exchange of health information between patients, practitioners and caregivers, regardless of time and location. In this perspective paper, we introduce to our digital strategy in Dresden to develop constantly the Multiple Sclerosis Documentation System (MSDS) into an eHealth platform which can be used for different purpose. Different user cases are presented implementing this software platform providing an important perspective of digital innovative patient management in future. The holistic MS patient management will have important impact on other fields of patient care as eg. neurorehabilitation.